IMPLEMENTASI LEMBAR KERJA PESERTA DIDIK (LKPD) BERORIENTASI MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK KELAS XI MIA 4 SMAN 9 PEKANBARU - Hidayah, Maulina; Fauziah, Yuslim; Wan Syafi’i, Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is purposed to improve critical thinking ability and learning result of students of class of XI MIA 4 SMAN 9 Pekanbaru with Student Worksheet implementation oriented on guided inquiry learning model . This research is class act research which is implemented in two cycles, each cycle consist of 4 steps they ara planning, implementation, observation, and reflection. Research subject is student of class of XI MIA 4 SMAN9 pekanbararu numbered 36 students consist of 17 male and 19 female. Parameter that measured is ability to think critical and student learning result consist of cognitive and affective of the student. Data collecting technique is done by test (Post test and daily test) and non test (observation sheet). Data analysis technique is done quantitatively and supported by descriptive analysis technique. Research result shown that average ability of thinking critically of students on cycle I is 80,90 with category of good and increased on cycle II to 85.05 with category of good. The average of absorption of student on cycle I is 79,17 with category of enough and increased in cycle II to 84.86 with category of good. For student learning on cylcle I learning is 86,11% and cycle II reached 100% done. While average of attitude score of student on cycle I is 79,26 with category of enough and increased on cycle II to 84,07 with category of good. Based on research result concluded that student worksheet implementation oriented on guided inquiry learning model can increased the ability of think critically and learning result of student of class of XI MIA 4 SMAN 9 Pekanbaru.Keywords : Student Worksheet, Guided Inquiry and Think Critically